PEMBERDAYAAN WILAYAH PERBATASAN NEGARA UNTUK MEMPERKUAT PERTAHAHAN NEGARA - Djuyandi, Yusa; Mustofa, Mustabsyirotul Ummah; Husin, Luthfi H.; Iriansyah, Moch Nurdi; Fajarudin, Arif (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Indonesia has a doctrine of the universal people's defence system (Sishanrata), which of it can be seen from the support of civil society in national defence. Civil society's support for national defence and national security can be seen from the perspective of civil-military relations in border areas. TNI and civil society communication in strengthening national resilience seek to provide a broader understanding of the importance of harmonious and strong civil-military relations in border areas, especially in this case in the Natuna region, Riau Islands as the outermost area of the state border. Cooperation between various stakeholders in border areas is required to improve synergistic relations between civil-military in dealing with threats in border areas. Thus, civil society is expected to have an active role in guarding border sovereignty. In addition, the TNI also needs to have good social communication skills with civil society as a supporting component of national defence in border areas. It is necessary to collaborate and cooperate between the TNI and civil society on an ongoing basis in Indonesia's border areas to provide benefits to the people at the border and contribute to efforts to strengthen national defence.